Implementasi Kebijakan Pengelolaan Sungai Kanal Banjir Barat Atau Kaligarang Di Kota Semarang - R. Harley Desmond D.P; Rina Martini; Nunik Retno H (Journal of Politic and Government Studies, 2015)
Management Policy Flood Canal River West / Kaligarang in Semarang isa policy made by the Government that the Government Regulation No. 38 of 2011 on the River Management Regulations as well as on River ManagementCooperation. This policy is a policy that has the objective to cope with the floodand improve the local economy through events and destinations new tourist attractions in the form of water attractions (Riverpark) in Semarang.This study is a qualitative study with the primary objective to describe thedepth of the River Management Policy Implementation West Flood Canal /Kaligarang in Semarang. Data collection techniques in this study using in-depthinterviews and documentation and analysis of documents. Analysis of the data in this study include stage data reduction, data presentation, and data verification orconclusion.From the results of this study concluded that the Policy ManagementFlood Canal River West / Kaligarang in Semarang has not run optimally, withindications that implementation is not fully maximized because they stagesocialization agencies / related local government offices in the preparation of the